2011
DOI: 10.1590/s1516-31802011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of digital mammography and film mammography: systematic review and meta-analysis

Abstract: CONTEXT AND OBJECTIVE: Mammography is the best method for breast-cancer screening and is capable of reducing mortality rates. Studies that have assessed the clinical impact of mammography have been carried out using film mammography. Digital mammography has been proposed as a substitute for film mammography given the benefits inherent to digital technology. The aim of this study was to compare the performance of digital and film mammography. DESIGN: Systematic review and meta-analysis. METHOD: The Medline, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
(70 reference statements)
0
20
0
3
Order By: Relevance
“…All SRs were on gynecological topics: teriparatide for osteoporosis in post-menopausal women (10), lapatinib for advanced or metastasized breast cancer (11), comparative evaluation of digital mammography and film mammography (12), colposcopic triage methods for grade 3 cervical intraepithelial neoplasia (CIN3) after a cytopathological diagnosis of a low-grade squamous intraepithelial lesion (13) and risk of persistent high-grade squamous intraepithelial lesion after an electrosurgical excision with positive margins (14). Three of the reviews focused on treatment (10,11,14), and two focused on diagnosis (12,13). Three of these SRs presented meta-analyses of their results (10,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…All SRs were on gynecological topics: teriparatide for osteoporosis in post-menopausal women (10), lapatinib for advanced or metastasized breast cancer (11), comparative evaluation of digital mammography and film mammography (12), colposcopic triage methods for grade 3 cervical intraepithelial neoplasia (CIN3) after a cytopathological diagnosis of a low-grade squamous intraepithelial lesion (13) and risk of persistent high-grade squamous intraepithelial lesion after an electrosurgical excision with positive margins (14). Three of the reviews focused on treatment (10,11,14), and two focused on diagnosis (12,13). Three of these SRs presented meta-analyses of their results (10,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…In screen-film mammography, images were developed and fixed chemically, a process similar to film photography. Processing errors led to > 20 percent of images being rejected, 10 resulting in repeat imaging which increased examination time, exposure to ionizing radiation, and costs. In the U.S., screen-film mammography has now largely been replaced by full-field digital mammography.…”
Section: Methods Of Breast Cancer Screeningmentioning
confidence: 99%
“…This percentage was applied to the overall number of interval cancers in the 20-year period and sensitivity was calculated. Sensitivity was assumed to be similar for both techniques [10][13] but was modeled as a probabilistic parameter and was sampled separately for each technique using the same statistical distribution with a mode of 86.66%. This allowed us to obtain scenarios with similar and different sensitivities favoring digital or screen-film mammography (see appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…The US Preventive Services Task Force recommendations [9], however, were based on the results of screening with screen-film mammography and consider that there is insufficient evidence to recommend digital mammography. The existing evidence on the effect of digital mammography in population-based breast cancer screening programs indicators is inconclusive: although the latest studies have found a slightly higher detection rate (number of cancers detected per 1,000 examinations) with digital mammography [10], the main conclusion of review studies is that digital mammography is at least as good as screen-film [11][13]. Recent studies in Spain [14][16] have found a lower recall rate (percentage of women called back for further tests) for digital mammography and a similar cancer detection rate.…”
Section: Introductionmentioning
confidence: 99%